Low-friction nanojoint prototype. (16th March 2018) - Vlassov, Sergei; Oras, Sven; Antsov, Mikk; Butikova, Jelena; Lõhmus, Rünno; Polyakov, Boris
Abstract: High surface energy of individual nanostructures leads to high adhesion and static friction that can completely hinder the operation of nanoscale systems with movable parts. For instance, silver or gold nanowires cannot be moved on silicon substrate without plastic deformation. In this paper, we experimentally demonstrate an operational prototype of a low-friction nanojoint. The movable part of the prototype is made either from a gold or silver nano-pin produced by laser-induced partial melting of silver and gold nanowires resulting in the formation of rounded bulbs on their ends. The nano-pin is then manipulated into the inverted pyramid (i-pyramids) specially etched in a Si wafer. Due to the small contact area, the nano-pin can be repeatedly tilted inside an i-pyramid as a rigid object without noticeable deformation. At the same time in the absence of external force the nanojoint is stable and preserves its position and tilt angle. Experiments are performed inside a scanning electron microscope and are supported by finite element method simulations.